The Impact of Mergers and Acquisitions on Firms’ Operating Performance: Evidence from Chinese Listed Companies. - Li, Ye (2014)
We examine 544 M&A transactions among Chinese companies listed on Shanghai and Shenzhen Stock Exchange during the period between 2011 and 2013. The methodology used is event study. Both short-term and long-term operating performances of acquiring companies are assessed using event study method. We use the Market Model is calculate the abnormal returns and abnormal returns of acquiring firms around announcement dates. For long-run analysis, we use the Market Model, CAPM and the buy-and-hold abnormal returns to investigate the performance of acquiring firms after M&A announcements. The test results show significantly positive cumulative abnormal returns around the announcements in the short term and some benefits from M&A in the long term with the approach of CAPM and the buy-and-hold returns. We also find that the cumulative abnormal returns are different when the payment method is different and when the stock type of target companies is different. The transactions that are completed by stock payment and that have public acquired firms usually gain better operating performance than the transactions completed by cash and private targets. Correspondingly, in the regression analysis, we suggest payment method and share type of acquiring firms have a significant influence on the operating performance in M&A activities.